CD300E+ macrophages facilitate liver regeneration after splenectomy in decompensated cirrhotic patients - Tao Yang; Yuan Zhang; Chujun Duan; Hui Liu; Dong Wang; Qingshan Liang; Xiao Chen; Jingchang Ma; Kun Cheng; Yong Chen; Ran Zhuang; Jikai Yin (Experimental and Molecular Medicine)
Abstract Liver cirrhosis is prognostically associated with poor life expectancy owing to subsequent liver failure. Thus, understanding liver regeneration processes during cirrhotic injury is highly important. This study explored the role of macrophage heterogeneity in liver regeneration following splenectomy. We collected detailed clinical information from 54 patients with decompensated cirrhosis before and after splenectomy. Obvious liver regeneration was observed after splenectomy in cirrhotic patients. Single-cell RNA sequencing (scRNA-seq) was performed on three paired liver tissues from patients before and after surgery to explore the immune microenvironment map and the characteristics of liver regeneration-associated macrophages (RAMs). scRNA-seq analysis revealed that the composition of hepatic immune cells changed after splenectomy; among these changes, the proportion of CD300E+ RAMs significantly increased after surgery, and high expression levels of functional genes associated with cell proliferation promoted liver regeneration. Moreover, a mouse model of carbon tetrachloride-induced cirrhosis and a coculture system consisting of primary bone marrow-derived macrophages and hepatocytes were established for validation. We observed a similar phenomenon of liver regeneration in cirrhotic mice and further confirmed that CD300E+ monocyte-derived macrophages facilitated hepatocyte NAD+ synthesis via the secretion of NAMPT, which subsequently promoted hepatocyte proliferation. This study characterized the hepatic immune microenvironment in patients with cirrhosis following splenectomy. Our findings demonstrated that CD300E+ macrophages play a crucial role in remodeling the hepatic immune microenvironment after splenectomy, thereby promoting liver regeneration in patients with decompensated cirrhosis. CD300E+ macrophages are anticipated to emerge as a novel therapeutic strategy for the treatment of liver cirrhosis.